2013
DOI: 10.7717/peerj.68
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression ofmiR-1, a putative tumor suppressing microRNA, in cancer resistant and cancer susceptible mice

Abstract: Mus spretus mice are highly resistant to several types of cancer compared to Mus musculus mice. To determine whether differences in microRNA (miRNA) expression account for some of the differences in observed skin cancer susceptibility between the strains, we performed miRNA expression profiling of skin RNA for over 300 miRNAs. Five miRNAs, miR-1, miR-124a-3, miR-133a, miR-134, miR-206, were differentially expressed by array and/or qPCR. miR-1 was previously shown to have tumor suppressing abilities in multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…More recently studies have found several other deregulated miRs in chordoma, including miR‐31, miR‐222, miR‐140‐3p, miR‐148a, and miR‐149‐3p . Among these miRs with deregulated expression in chordoma, miR‐1 is a validated and frequently downregulated in various types of cancer . In the present study, we characterized 35 chordoma specimens and extracted RNAs to quantify the relative expression level of miR‐1.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…More recently studies have found several other deregulated miRs in chordoma, including miR‐31, miR‐222, miR‐140‐3p, miR‐148a, and miR‐149‐3p . Among these miRs with deregulated expression in chordoma, miR‐1 is a validated and frequently downregulated in various types of cancer . In the present study, we characterized 35 chordoma specimens and extracted RNAs to quantify the relative expression level of miR‐1.…”
Section: Discussionmentioning
confidence: 84%
“…The results showed miR‐1 expression was inversely correlated with Met expression; expression of miR‐1 was lower in chordoma tissues and was coupled with high expression of Met. These results are consistent with studies in other types of human cancers such as colorectal tumors which also show that miR‐1 and Met are often concomitantly deregulated …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Tumor suppressive functions of miR-1 have been demonstrated in numerous human malignancies (17, 39-41). Its action was associated with direct targeting of several oncogenes, including MET (30) – one of the crucial oncogenic drivers in GBM.…”
Section: Discussionmentioning
confidence: 99%